Effect of inhaled iloprost on gas exchange in inhalation injury. Issue 2 (October 2017) - Newsome, Andrea Sikora; Sultan, Said; Murray, Brian; Jones, Samuel W.; Pappas, Ashley; Schmidt, Keith T.; Filteau, Guillaume; Laux, Jeffrey P.; Wolfe, Adam; Williams, Felicia; Cairns, Bruce A.
Highlights: First study to evaluate inhaled iloprost in burn patients with inhalation injury. Inhaled iloprost reduces ventilation-perfusion mismatch without adverse effects. Inhaled iloprost is associated with significantly improved oxygenation. Abstract: Objective: Inhalation injury is an independent risk factor for mortality in burn patients. The purpose of this study was to observe the effect of inhaled iloprost on gas exchange in patients with inhalation injury and acute respiratory failure as measured by an improved PaO2 /FiO2 ratio. Methods: Patients admitted to the burn intensive care unit from 2013 to 2014 meeting Berlin criteria for acute respiratory distress syndrome (ARDS) with a diagnosis of inhalation injury and who received inhaled iloprost were included. Medical records were reviewed to collect patient demographics, characterize iloprost prescribing practices, and observe changes in oxygenation and hemodynamic status after iloprost administration. Differences were evaluated using a t -test with cluster corrected standard errors. Results: A total of eight patients were included with 157 different PaO2 /FiO2 ratios calculated. All patients had moderate or severe ARDS with a baseline PaO2 /FiO2 ratio of 131.9 mmHg (IQR 119.3–197.3). Median duration of iloprost therapy was 5 days (IQR ± 7). A statistically significant increase in PaO2 /FiO2 ratio was observed after iloprost administration with a mean increase of 9.7 mmHg (95% CI 1.8–17.7, p = 0.023). Inhaled iloprost had no effect on hemodynamic parameters. Conclusions: Inhaled iloprost for inhalation injury and ARDS after burn injury was associated with a small but statistically significant improvement in oxygenation.